Prevalence of Helicobacter pylori infection in China: A systematic review and meta‐analysis - Ren, Shuai; Cai, Pengpeng; Liu, Yaqian; Wang, Tianpei; Zhang, Yan; Li, Qian; Gu, Yuanliang; Wei, Liqin; Yan, Caiwang; Jin, Guangfu (Journal of gastroenterology and hepatology, 2022)
Background and Aim Helicobacter pylori (H. pylori) infection rates have been changing with different populations and geographic areas. We systematically evaluated the longitudinal trends in H. pylori prevalence in China over the past decades. Methods We performed a systematic review of literature reporting the prevalence of H. pylori infection in mainland China from 1990 to 2019 in the PubMed and China National Knowledge Infrastructure databases. We conducted a meta‐analysis of qualified studies using a random effects model to estimate the pooled prevalence with a 95% confidence interval (95%CI). Results A total of 412 eligible studies with 1 377 349 subjects were included. The pooled H. pylori prevalence was 44.2% (95%CI: 43.0–45.5%) in mainland China, with an estimated 589 million individuals infected with H. pylori. The prevalence was relatively high in the Northwest (51.8%, 95%CI: 47.5–56.1%), East (47.7%, 95%CI: 45.4–50.0%), and Southwest China (46.6%, 95%CI: 42.1–51.1%). The prevalence significantly decreased from 58.3% (95%CI: 50.7–65.5%) in the period 1983–1994 to 40.0% (95%CI: 38.2–41.8%) in the period 2015–2019. The prevalence increased with age, ranging from 28.0% (95%CI: 23.9–32.5%) in children and adolescents to 46.1% (95%CI: 44.5–47.6%) in adults. Conclusion Although the burden of H. pylori infections is still huge in China, the infection rate has been decreasing over the past decades. Targeted H. pylori eradication strategies may be considered in areas or populations with a high incidence of gastric cancer.